ANALISIS DAMPAK WORK-LIFE BALANCE DAN STRES KERJA TERHADAP KEPUASAN KERJA KARYAWAN GENERASI Z DI DENPASAR - I Putu Rika Yasa Puta; Putu Ratna Juwita Sari (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the effect of work-life balance and job stress on job satisfaction among Generation Z employees in Denpasar City. The research method used is a quantitative approach, with data collected through questionnaires distributed to respondents categorized as Generation Z. Data analysis was conducted using multiple linear regression to determine the influence of independent variables on the dependent variable. The results show that work-life balance has a positive and significant effect on job satisfaction, while job stress has a negative and significant effect on job satisfaction. Simultaneously, work-life balance and job stress have a significant effect on job satisfaction among Generation Z employees in Denpasar City. In conclusion, better work-life balance leads to higher job satisfaction, while higher job stress tends to reduce job satisfaction. Therefore, organizations should pay attention to employees’ work-life balance and manage job stress effectively to improve job satisfaction.